Aberrant expression of LncRNA CASC2 mediated the cell viability, apoptosis and autophagy of colon cancer cells by sponging miR‐19a via NF‐κB signaling pathway. Issue 3 (13th May 2021) - Zhang, Peng; Pan, Yan; Sun, Jujun; Pan, Gaiyan
Abstract: Abnormal and rapid proliferation of colon cancer cells is a severe problem that can be regulated by non‐coding RNAs. Thus, our study focused on effects of lncRNA CASC2 and miR‐19a on colon cancer cells. Expressions of lncRNA CASC2, miR‐19a, Bcl‐2, Bax and NF‐κB/p65 were examined by RT‐qPCR. Cell viabilities were detected by CCK‐8. A luciferase report assay was used for measuring binding conditions between lncRNA CASC2 and miR‐19a. Western blotting was used to evaluate expression of LC3‐I, LC3‐II and p62 related to autophagy. Expression of lncRNA CASC2 lower in cancer cell lines and the overexpression reduced the cell viability of HT29 and SW480. Furthermore, Bcl‐2 was suppressed by overexpressed lncRNA CASC2, while Bax was upregulated. LC3‐Ⅰ and p62 were both inhibited, but LC3‐Ⅱ was promoted. MiR‐19a was predicted to bind lncRNA CASC2 and expressed higher in cancer cell lines. Overexpressed miR‐19a reduced expression of lncRNA CASC2 and increased cell viability. This was repressed by upregulated lncRNA CASC2. Bcl‐2 and Bax expression and proteins implicated in autophagy that are regulated by lncRNA CASC2 upregulation were reversed by miR‐19a overexpression. NF‐κB was upregulated in colon cancer cell lines, while inhibition of NF‐κB reversed functions of lncRNA CASC2 and magnified roles of miR‐19a. Our findings showed that lncRNA CASC2 inhibited cell viability in colon cancer cell lines and miR‐19a reversed its functions through the NF‐κB signalling pathway, suggesting that these could be factors in treating colon cancer in the future.